History as a Way to Emancipation - Stobiecki, Rafał (Sensus Historiae, 2019)
Since very long, history has been playing manifold functions: identifying, cognitive, didactic and legitimizing. The aim of the paper is to formulate several remarks on its (especially important nowadays) emancipatory function. The author adduces examples from both Polish and universal historiography aiming at showing how, in the historiographical praxis of the historians of both sexes, emancipatory claims appeared. Understanding history as a way to emancipation is affected by some ambivalence. On the one hand, within this reflection, speaking up for the groups is visible that have been disregarded, marginalized or persecuted. On the other hand, history regarded in these terms discloses, once more, its bearing upon ideology. It shows that there is no history which is innocent, objective and unentangled with the relations of the political power with science.